Clinical presentation and imaging findings in juvenile-onset back pain: a ten-year hospital-based retrospective analysis in Douala (Cameroon) - Kemta Lekpa, Fernando; Eloundou, Paul; Moulion Tapouh, Jean Roger; Simeni Njonnou, Sylvain Raoul; Fojo Talongong, Baudelaire; Same Bebey, Francine; Megne Tamo, Estelle; Noukeu, Diomède; Enyama, Dominique; Abouame, Palma Haoua; Sime Tchouamo, Arielle Annick; Namme Luma, Henry; et al. (Frontiers in Pediatrics, 2024)
Introduction. Studies exploring the clinical and imaging characteristics of juvenile-onset back pain (JOBP) are scarce. The purpose of this study was to assess the clinical presentation, imaging findings, and factors associated with JOBP. Methods. A retrospective record-based study was conducted among all paediatric cases presenting to the Rheumatology unit of the Douala General Hospital, Cameroon, from January 2014 to December 2023. The study did not include children whose back pain began after 16 years of age. Results. Of the 216 records of patients under 18 examined, 67 children (31 girls) were diagnosed with JOBP. The median age was 15 [13-16] years. More than two-third of the children included in this study had chronic pain (n = 46; 68.65%). Pain was mild to moderate in intensity in 48 children (71.6%). Radiculopathy was present in 10 children (14.92%). The most common location of back pain was the lumbar region (n = 64; 95.52%). Some children experienced pain in more than one location. The location of the pain was not associated with gender, duration of the pain, radiculopathy, or practice of a competitive sport (p>0.05). Musculoskeletal abnormalities on imaging were found in 38 children (62.29%). In multivariate analysis, peripheral joint involvement [aOR = 0.253 (0.073-0.878); p=0.030] and mild pain intensity [aOR = 0.077 (0.014-0.422); p=0.003], were independently associated with the presence of musculoskeletal abnormalities on imaging. Conclusion. JOBP affectsed a on third of children and adolescents of our clinic population. The common musculoskeletal abnormalities found on spine imaging were are disc diseases and scoliosis.